Improving Students’ Reading Skill Using The Little Prince Novel - Aswir Aswir; Muhamad Sofian Hadi; Nurul Laily (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
This study aims to investigate the effectiveness of using The Little Prince Novel to improve students’ reading skill. Participants in this study were 35 students of grade 11 IPA at Madrasah Aliyah Miftahul Umam. To find out this, a pretest was carried out to determine the students’ ability to read before using the novel, then do the treatment using a novel. Finally, a post test was performed to assess the level of reading achievement of students. The method of this research is quantitative and using a pre-experimental design. The average of pre-test was 64.57 and the average of post-test was 89.37. It is significantly different from the result of pre-test and post-test scores. The results of the pre-test and post-test were calculated using SPSS 22. The significant is equal to 0.00 with significant level a = 0.05 (2-tailed). Since the score is 0.00 < a (0.05), H1 was accepted and H0 was rejected. It was found that substantial students’ outcomes were seen, an improvement in the value of reading skill assessment was shown, which meant that the novel could enhance the learners’ reading ability.